Genre containers: Building a theoretical framework for studying formats in information behavior. (26th October 2021) - Brannon, Brittany; Buhler, Amy G.; Cataldo, Tara Tobin; Faniel, Ixchel M.; Connaway, Lynn Silipigni; Valenza, Joyce Kasman; Cyr, Christopher
Abstract: Prior studies have shown high‐level differences in people's perception and use of various information formats. However, the lack of a coherent and theoretically informed framework of elements of format has inhibited a nuanced understanding of the role that formats play in information behavior. This paper draws on theories from the field of rhetoric and composition to ground the study of information format in a social constructivist perspective that foregrounds action in context. Specifically, rhetorical genre theory is discussed in detail and the limitations of previous information behavior studies using rhetorical genre theory are explored. One of the main problems of earlier studies is confusing genres and their containers. This paper introduces and defines the concept of containers as typified ways of collecting and presenting texts of certain genres for publication. Building on rhetorical genre theory, the paper offers a theoretical exploration of the role that containers play in the formal and/or public sharing of information within discourse communities. An illustrative example of the concepts applied to data from an Institute of Museum and Library Services funded study is provided.